Thermally-induced agglomeration tailors the stability of Pt SAs on TiO2 and use in photocatalytic H2 generation - Will, Johannes; Denisov, Nikita; Qin, Shanshan; Wu, Mingjian; Wang, Yue; Kim, Hyesung; Karpstein, Nicolas; Dierner, Martin; Schmuki, Patrik; Spiecker, Erdmann (Journal of Materials Chemistry A, 2025)
Thermally-induced agglomeration of Pt single atoms (SAs) on anatase TiO2 thin films is exploited for tuning their activity in photocatalytic H2 generation. After thermal treatment at temperatures ranging from 350 to 650 °C in an Ar atmosphere, a more than fivefold higher photocatalytic activity is achieved under optimized conditions. The Pt species obtained after annealing at different temperatures are monitored via ex situ and in situ transmission electron microscopy. For in situ measurements, a gas cell system operating at 700 mbar is utilized. Structural data obtained in the temperature range from 250 to 950 °C demonstrate the co-existence of SA species and agglomerates over the whole temperature range, and give fundamental insights into thermal and light-induced agglomeration processes, including nucleation, growth and ripening of Pt species on TiO2. Under optimized annealing conditions Pt is present as a mixture of SAs, 2D rafts and nanoparticles. Data show that annealing can stabilize the Pt species against light-induced agglomeration and detailed analysis reveals such SAs (realized under optimized annealing conditions) provide the most active sites (in comparison with various agglomerates). We further emphasize the importance of conducting atomic-scale structural characterization both before and after photocatalysis to accurately establish the process-structure-property-performance relationships of SAs in photocatalysis.
CRIS-Team Scopus Importer:2025-04-11